2009
DOI: 10.1007/s11814-009-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Separation and characterization of bitumen from Athabasca oil sand

Abstract: Separation and chemical analysis was investigated using bitumen samples from Athabasca oil sand in Alberta. Fractionation according to solubility and polarity has been used to separate bitumen into its fractions. The solvent de-asphaltening was performed by n-pentane solvent (solubility fractionation), and the polarity fractionation using Fuller's earth allows maltene to separate into SARA components (saturates, aromatics, resins and asphaltenes). The SARA components are analyzed comprehensively using elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 25 publications
3
58
0
2
Order By: Relevance
“…Strausz et al (2010) described bitumen as the heaviest form of petroleum which is viscous, black and sticky. It is a complex mixture of high boiling point range of hydrocarbon compounds and molecules with relatively low hydrogen to carbon ratio (Yoon et al, 2009). The exploitation and exploration of the Nigerian natural bitumen deposits can best be described to be at the planning stage.…”
Section: Microbial J 1 (4): 139-148 2011mentioning
confidence: 99%
“…Strausz et al (2010) described bitumen as the heaviest form of petroleum which is viscous, black and sticky. It is a complex mixture of high boiling point range of hydrocarbon compounds and molecules with relatively low hydrogen to carbon ratio (Yoon et al, 2009). The exploitation and exploration of the Nigerian natural bitumen deposits can best be described to be at the planning stage.…”
Section: Microbial J 1 (4): 139-148 2011mentioning
confidence: 99%
“…In this figure, absorbance peaks appeared at 2924, 2855, 1458 and 1376 cm -1 , which corresponded to the aliphatic hydrogen for C-H stretching in -CH 3 and -CH 2 in TMA. 13 These bands are commonly observed in TMA and p-TMA as shown in Figure 1. Also, the peaks near 1029 and 1300 cm -1 were attributed to -C-O and -C-N vibration in TMA and p-TMA, respectively.…”
Section: Methodsmentioning
confidence: 88%
“…The band around 3500 cm -1 corresponded to N-H stretching in two molecules. 13 In IR spectra of p-TMA, particularly, the peak at 1601 cm -1 associated with C=C stretching mostly disappeared in p-TMA, indicating that TMA was polymerized. From above NMR and IR measurements, it was confirmed that polymerization using AIBN initiator was well conducted.…”
Section: Methodsmentioning
confidence: 93%
“…The Iatroscan MK 5 Thin Layer Chromatography (TLC) was used for the chemical characterisation of bitumen by separating it into four fractions: Saturates, Aromatics, Resins and Asphaltenes (SARA) [19]. During the measurement, the separation took place on the surface of silica-coated rods.…”
Section: Sara Determinationmentioning
confidence: 99%